2010
DOI: 10.1890/09-1548.1
|View full text |Cite
|
Sign up to set email alerts
|

Small‐scale genetic structure in a marine population in relation to water circulation and egg characteristics

Abstract: Abstract. Until the last decade it was assumed that most marine species have pronounced gene flow over vast areas, largely because of their potential for dispersal during early life stages. However, recent genetic, modeling, and field studies have shown that marine populations may be structured at scales that are inconsistent with extensive dispersal of eggs and larvae. Such findings have stimulated the birth of new studies explaining the mechanisms that promote population structure and isolation in the oceans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 40 publications
(48 reference statements)
3
50
0
Order By: Relevance
“…In contrast, when comparing among sheltered areas, correlations in recruitment decreased rapidly with distance, remaining above background levels essentially only for stations sampled within a single fjord. An analysis of egg buoyancy and circulation patterns within fjords found that eggs are concentrated in inward-flowing currents, acting as a retention mechanism for eggs spawned locally within fjords (Ciannelli et al 2010). Tagging studies on recently settled age-0 cod also indicate that this early life stage is very stationary (Grant & Brown 1998, Olsen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, when comparing among sheltered areas, correlations in recruitment decreased rapidly with distance, remaining above background levels essentially only for stations sampled within a single fjord. An analysis of egg buoyancy and circulation patterns within fjords found that eggs are concentrated in inward-flowing currents, acting as a retention mechanism for eggs spawned locally within fjords (Ciannelli et al 2010). Tagging studies on recently settled age-0 cod also indicate that this early life stage is very stationary (Grant & Brown 1998, Olsen et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Marine reserves are increasingly being implemented to aid in the conservation and recovery of exploited populations; however, the effectiveness of marine reserves depends critically on the spatial scale of processes such as larval and adult dispersal (Botsford et al 2003, Kritzer & Sale 2004, Grüss et al 2011. In 2012, Norway's first no-take marine reserve was established in the Tvedestrand fjord between our Arendal and Risør study sites, spanning 1.5 km 2 of the inner fjord habitat and including a major cod spawning and nursery area (Ciannelli et al 2010). Marine reserves are generally not considered for highly migratory species such as Atlantic cod, but what we now know about movement and dispersal of Skagerrak coastal cod suggests that even a relatively small reserve could be an effective conservation tool in this region, protecting sedentary adults from harvest (see also Moland et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the early days of this survey, the spatial structuring of populations within and among fjords has been evident (21), and recently supported by genetics (22,23) and life-history studies (17,24). This structure is maintained through retention of early life-history stages (eggs and larvae) (25) and limited juvenile and adult dispersal (26,27). Spatial population structure can provide stabilizing benefits to fisheries and ecosystems (28,29) but is not always considered in management of fish stocks or incorporated into ecological studies.…”
mentioning
confidence: 83%